Wood Micro Structural Studies of Indian Rutaceae Part IV: Tribe Zanthoxyleae - Bhardwaj, Nisha; Gupta, Sangeeta (Indian Forester, 2009)
The present study deals with the detailed wood anatomy of the 9 Indian species of 3 genera viz. Melicope Forst., Tetradium Hook. and Zanthoxylum Linn. belonging to the tribe of Zanthoxyleae of the family Rutaceae. The results are summarized in the tables and identification key has been developed for the separation of all the 10 species of this tribe. Photomicrographs have been given for the diagnostic features. The woods of this tribe are used for planks, rafters, match splints, plywood, cabinet work, axe handles, legs of beds, chair and packing cases. The wood anatomical parameters suggest that the tribe Zanthoxyleae is a heterogeneous tribe characterized by ring to diffuse porous woods; growth ring distinct to indistinct distinct due to marginal bands of parenchyma; simple to reticulate perforation plate; coalescent aperture; inter vessel pits minute to small; fibres non-septate. Almost all type of parenchyma present in all the species. Rays homogeneous to heterogeneous. Prismatic crystals in rays present in all the species except Melicope lunuankenda, Z. rhetsa and Z. oxyphyllum. Silica bodies present in fibres, rays and parenchyma in Melicope lunuankenda and Tetradium fraxinifolium. New reports include coalescent aperture in the entire family. Crystals in fibres and silica bodies reported for the first time of Tetradium and Melicope.